Limiting the reproductive activity of bee colonies as a biotechnological method for increasing their vitality and productivity - Postoienko, Hanna; Mishchenko, Oleksandr; Postoienko, Volodymyr; Lytvynenko, Olesya; Bodnarchuk, Gennadіy; Kryvoruchko, Dmytro; Afara, Kristin (Ecological Questions, 2025)
The intensity of development and productivity of the bee colony throughout the entire active period of its life depends on the physiological state of bees and their number in the nest. The tasks set in the work were solved experimentally using the following research methods: zootechnical (selection of groups of analogues, study of the development and productivity of bee colonies), mathematical-statistical (assessment of the reliability of the obtained results). Biometric data processing was performed on a PC using MS Excel software with the use of built-in statistical functions. In the presented work, the data of experimental research on the mechanisms of influence of methods of isolation and replacement of queen bees on the functional state of bee colonies and the dynamics of nectar flow, as well as their functional state after the end of honey collection, was provided. Along with the state of bee colonies and productivity, the degree of development of such an anatomical organ of bees as the fat body was evaluated. During the study, it was established that after the replacement of queen bees with queen cells, the nectar flow decreased in all experimental groups, but after the release of queen bees from the queen cells, the amount of nectar brought by bees increased. A high degree of fat body development was observed among bees where queen bees were isolated. The development of the fat body among the bees of other experimental groups during the experimental period was almost identical. The degree of development of the fat body affected the honey collection of bee colonies. A long isolation of queen bees negatively affects their reproductive capacity. It has been experimentally proven and recommended to use methods of isolation and replacement of queen bees for the period of short honey collections – up to 15 days. Planting a fertile queen bee in a bee colony is the highest-priority option. The proposed biotechnological techniques will make it possible to use the potential of bee colonies, to keep bees with a longer lifespan and to increase the yield of marketable honey per bee colony.